Exercise capacity in the stair-climbing test predicts outcomes of operable esophageal cancer in minimally invasive era. Issue 3 (March 2022) - Junttila, Anna; Helminen, Olli; Mrena, Johanna; Sihvo, Eero
Abstract: Introduction: The risk of complications after esophagectomy highlights the need for careful preoperative assessment. Aim was to assess whether stair-climbing test (SCT) could predict outcomes of patients with operable esophageal cancer in minimally invasive era. Materials and methods: Patients with esophageal cancer were evaluated for surgical treatment in Central Finland Central Hospital from 2012 to March 2021. Of evaluated 162 patients, 138 were scheduled to eventually undergo surgery. The exercise capacity was evaluated with symptom limited SCT. Patients were divided into four study groups on intent-to-treat basis: surgery and the SCT >14 m (Group 1), surgery and the SCT <11 m (Group 2), non-surgical therapy and the SCT <11 m (Group 3) and non-surgical therapy and the SCT >14 m (Group 4). Results were adjusted for confounders. Results: Major complication rate was 10.1% vs 40.0% between Group 1 and 2 (p = 0.006), and 90-day mortality 0% vs 20.0% (p < 0.001). Overall survival rates in Groups 1–4 at 1-year were 92.3% vs 72.2% vs 46.8% vs 81.8%, at 3-year 68.5% vs 52.7% vs 15.6% vs 27.3% and at 5-year 58.7% vs 39.5% vs 0% vs 0%, respectively (p < 0.001). In adjusted analysis when compared to Group 1, other groups had increased 5-year mortality hazard (Group 2 HR 2.88 (95% CI 1.25–6.63), Group 3 HR 15.6 (95% CI 5.57–43.5) and Group 4 HR 5.35 (95% CI 2.08–13.7)). Conclusion: Exercise capacity measured with SCT in esophageal cancer patients is a strong predictor of complications and survival, and is a potential parameter to be included in any risk or prognostic models.